PERMAINAN BAHASA (SEBUAH TINJAUAN GRAFOLOGIS DAN FONOLOGIS) - Mikael Depari, Obat (Widya Warta, 2011)
Language play is now in common practice among various levels of society, ranging from the men in the street up to well-educated individuals, and from jobless persons up to professionals. It even gets more popular in line with the development of information and communication technology. Language play occurs when people manipulate the forms and functions of language. Formally, language play makes use of numbers and letters to reveal certain meanings different from those in their conventional application. Functionally, language is manipulated in such a way that it may attract readers’ attention and amuse them as well. This article is an attempt at characterizing the phenomenon of language play and examines the ways in which the language is manipulated to create a new style of language usage. The discussion on language play here is graphological and phonological in nature. In other words, it discusses language play in terms of its writings and sounds. The corpus of the discussion are words, phrases, and sentences in English, Indonesian, Javanese, and Batak. They are taken from playful personalized car licence-plates, advertisements, graffiti, books, televisions, public places, etcetera. The findings suggest that language play can help people to communicate their ideas through some unique forms of language. Besides, it may also be a source of fun both for themselves and for others.